Highly Active Carbon/a-MnO2 Hybrid Oxygen Reduction Reaction Electrocatalysts - Chen, G.; Sunarso, J.; Zhu, Y.; Yu, J.; Zhong, Y.; Zhou, W.; Shao, Zongping (Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim, 2016)
© 2016 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.Manganese oxides are attractive catalyst candidates for the oxygen reduction reaction (ORR) given their natural abundance and low toxicity. a-MnO2, in particular, exhibits high ORR activity in an alkaline medium. The hybrid concept provides a way to obtain enhanced ORR performance and long-term durability through an optimized metal oxide-support interaction. Herein, we synthesized a carbon nanotube (CNT)-graphene-a-MnO2 hybrid in a hydrothermal reaction in which the MnO2 nanosheets were deposited on the interior and exterior surfaces of the CNT channels. The resultant hybrid displayed very high ORR activity that is only marginally less than the performance of a commercial 20wt% Pt/C catalyst and showed even better stability. The excellent ORR activity was attributed to two main factors, that is, the mesoporous architecture of the catalyst and the strong electron coupling between the encapsulated metal oxide and the support. We also showed that the preferential deposition of MnO2 nanosheets within the CNT channels provides enhanced ORR performance relative to deposition on the exterior surfaces of the channels only. This in turn demonstrates unequivocally the confinement effect that the CNT exerts on the encapsulated metal oxide component, which can be exploited as a route to enhanced ORR activity.